Vietnam's second front : domestic politics, the Republican Party, and the war - Johns, Andrew L., 1968- (University Press of Kentucky, 2010)
The Vietnam War has been analyzed, dissected, and debated from multiple perspectives for decades, but domestic considerations-such as partisan politics and election-year maneuvering-are often overlooked as determining factors in the evolution and outcome of America's longest war. In Vietnam's Second Front: Domestic Politics, the Republican Party, and the War, Andrew L. Johns assesses the influence of the Republican Party- its congressional leadership, politicians, grassroots organizations, and the Nixon administration-on the escalation, prosecution, and resolution of the Vietnam War. This groun.